Analisis Hasil Uji Keterbacaan Petunjuk Praktikum Ekologi: Studi Kasus dengan Partisipasi 15 Mahasiswa - Efendi, Rusnadi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
This study aims to analyze the readability test results of ecology practicum instructions among students, involving the participation of 15 students. The research design used was descriptive research. The method employed included measuring the comprehension level through readability tests of the provided ecology practicum instructions. The research findings indicate that 90% of the 15 students achieved a good level of comprehension of the ecology practicum instructions provided. These findings suggest that the development and presentation strategies of ecology practicum instructions can play a crucial role in enhancing students' understanding of ecology practical materials. The implications of this study underscore the importance of attention to the design of practicum instructions that support effective learning in ecology within the context of higher education.